Epithelial-Mesenchymal Transition and Tumour Progression: An Overview - I. Al-Janabi, Ismail (Al-Rafidain Journal of Medical Sciences ( ISSN 2789-3219 ), 2023)
Aim: The purpose of this review is to highlight the role of the epithelial-mesenchymal transition (EMT) in tumorigenesis and assess the value of manipulating this process in cancer therapy. Method: A search was conducted for peer-reviewed articles in PubMed, Google Scholar, and ResearchGate employing keywords and phrases. Main Points: The EMT program is a key driver of tumor initiation and progression. Inhibition of EMT in carcinoma cells can yield fruitful results in the treatment of cancer, particularly in overcoming resistance to chemotherapy and precision drugs. Conclusion: Blocking the process of EMT in carcinoma cells can help overcome the resistance to chemotherapy and targeted precision medicine.